FeCoNiCrAl0.6 high-entropy alloy coating on Q235 steel fabricated by laser cladding. Issue 6 (13th April 2023) - Yuan, Shuhan; Li, Hailong; Han, Chengfu; Li, Wenqiang; Xu, Xiaofei; Chen, Chen; Wei, Ran; Wang, Tan; Wu, Shaojie; Li, Fushan
Abstract : To improve the surface properties of engineering components, FeCoNiCrAl0.6 high-entropy alloy (HEA) coating was prepared on Q235 steel by the laser cladding method. The results indicate that the phase constitution of this HEA coating is mainly a dual-phase structure dominated by face-centred cubic (FCC) solid solution. Moreover, the coating exhibited good corrosion resistance in both 3.5 wt-% NaCl and 0.1 mol L –1 HCl solutions, which can be attributed to the small Volta potential difference (∼20 mV) between the FCC phase and the body-centred cubic phase. This work confirms that the corrosion resistance of Q235 steel can be greatly improved by coating with a FeCoNiCrAl0.6 HEA, providing a novel route to further develop HEA coatings with excellent corrosion resistance.